Ultrasonic Cavitation‐Assisted and Acid‐Activated Transcytosis of Liposomes for Universal Active Tumor Penetration. (19th June 2021) - Wang, Guowei; Zhang, Chao; Jiang, Yifan; Song, Yue; Chen, Jifan; Sun, Yu; Li, Qunying; Zhou, Zhuxian; Shen, Youqing; Huang, Pintong
Abstract: Active tumor penetration has been recently recognized as a promising strategy to resolve the limitation of nanomedicine in terms of tumor penetration, but it is challenging to develop active transporting nanocarriers. Here, an ultrasonic cavitation‐assisted and acid‐activatable active transporting liposome for a broad range of tumors is reported. The active transporting liposome (size and charge dual‐conversional gemcitabine prodrug‐integrated liposomal nanodroplet (SCGLN)) overcomes the tight blood vessel walls with the aid of ultrasonic cavitation. The SCGLN subsequently transforms from micro‐size to nano‐size under prolonged ultrasound radiation. Once in the acidic tumor microenvironment, the nanosized SCGLN undergoes negative‐to‐positive charge‐reversal and triggers the cationization‐initiated transcytosis to penetrate deep into tumor parenchyma. The gemcitabine‐loaded SCGLN exhibits potent antitumor activity in multiple poorly permeable tumor models, which completely erases subcutaneous U251 glioma and stops the progression of orthotopic BxPC3 pancreatic ductal adenocarcinoma. This study presents a promising and universal strategy to develop active penetrating nanomedicines for efficient drug delivery in the low permeable tumor. Abstract : An active transporting liposome (size and charge dual‐conversional gemcitabine prodrug‐integrated liposomal nanodroplet (SCGLN)) is capable of ultrasound‐stimulated size transformation and acidity‐triggered charge conversion. The SCGLN overcomes the tight blood vessel walls with the aid of ultrasonic cavitation to enhance tumor accumulation, and subsequently undergoes negative‐to‐positive charge‐reversal and triggers the cationization‐initiated transcytosis to penetrate deep into tumor parenchyma, generating potent anticancer activity.